Use of nutritional supplements and other complementary medicine methods among patients with Parkinson’s disease in Lithuania - Guk, Jevgenija; Kaladytė Lokominienė, Rūta; Jatužis, Dalius (Frontiers in Neurology, 2025)
Background and purposeMore than half of Parkinson’s (PD) disease patients use nutritional supplements and other methods of complementary medicine (CAM). Only a minority discuss their use with their physician. We aimed to evaluate the prevalence and factors associated with using CAM and nutritional supplements among PD patients in Lithuania.MethodsThe cross-sectional study was conducted at Vilnius University Hospital Santaros Klinikos in 2022. Patients diagnosed with PD were asked to complete the questionnaire about nutritional supplements and CAMs used during the past 12 months.ResultsThe data analysis included 169 out of 206 questionnaires. There were 81 (47.9%) males and 88 (52.1%) females. The median age was 66 years old (IQR 59.5–72), and the median duration of PD was 4 years (IQR 2–8). One hundred six patients (62.7%) took nutritional supplements during the last 12 months, and 52 (30.8%) have used some other kind of CAM. Females used such treatment more often than males, respectively, 70.5% vs. 54.3%, p = 0.03 for nutritional supplements, and 38.6% vs. 22.2% (p = 0.021) for other CAM methods. There were no differences in other sociodemographic and disease-related characteristics between nutritional supplements and other types of CAM users and nonusers. Vitamin D, fish oil, and magnesium were the most frequently used supplements (respectively by 60.4, 51.4, and 54.7% of supplement users). Only 50 (47.1%) nutritional supplements and 35 (67.3%) CAM users discussed using such treatment with their neurologist or treating physician.ConclusionNutritional supplements and CAM therapies are frequently used by PD patients in Lithuania, with a higher prevalence among females. While 67.3% of CAM users discussed their usage with a treating physician or neurologist, only 47.1% of nutritional supplement users did the same. Nevertheless, the latter has a greater potential for interaction with conventional treatments. There is a need to expand the education of general practitioners, neurologists, and PD patients about the indications, effects, and possible side effects of nutritional supplements and other CAM methods, thus raising awareness and encouraging better communication regarding these measures.